Assessing the Potential Consequences of Climate Destabilization in Latin America - Vergara, Walter (World Bank, Washington, DC, 2014)
Estimating the potential costs of climate destabilization is not a trivial matter. Potential climate impacts have multiple consequences, some of which can be monetized while others are beyond the reach of standard economic tools. A full assessment of the implications of climate impacts often cannot be completed because many of the consequences are only partly known. This report summarizes data recently made available, through the portfolio of adaptation activities in the region, on some of the damages induced by climate destabilization. These include impacts from hurricane intensification, glacier retreat, and increased exposure to tropical vector diseases, coral bleaching, and composite costs of climate change in the particularly vulnerable Caribbean Basin. Other costs are becoming evident but they still cannot be estimated. Most worrisome among these are the potential implications from Amazon dieback which, if realized, will drastically affect the water cycle in the region as well as environmental services essential to economic activity in the region, with wider global implications. The report refers to destabilization in the title as recognition, that the region is now facing impacts from major, destabilizing changes in its climate.